Telecom Industry Brand Image and the Extended Service Marketing Ps: A Study on Private University Students of Rajshahi - Sarker, Md. Omar Faruk (American Journal of Trade and Policy, 2019)
Marketing always looks forward to making consumers delighted. Mobile telecom service provided a pace in daily life in Bangladesh. It plays a vital role in all the dimensions of our life. The prime objective of the study is to measure the influence of people, process, and physical evidence on brand image in the mobile telecom industry at Rajshahi metropolitan area in Bangladesh. One hundred fifty samples drawn from the students of two private universities using a convenient sampling technique. A structured questionnaire used for the survey. The findings of this study represent that all the null hypotheses rejected; there is a significant relationship between three extended service marketing and brand image in the mobile telecom industry. The researcher believes that this study would help strategy planners of mobile telecom service operators in Bangladesh to study people, process, and physical evidence with keen interest to blend service marketing mix and create and increase brand image as well as open more research relating to this ground. This finding may help different mobile telecom operators in Bangladesh to improve their focus regarding the efficient use of service marketing mix.